Resistant Bacteria vs. Public Health – A Review - Sienkiewicz, Michał; Klimas, Filip; Rusiński, Kacper; Zatłoka-Mazur, Dorota; Pawłowski, Bartosz; Zięba, Zuzanna; Potoczek , Adriana; Pudełko , Iwona (Quality in Sport, 2025)
Currently, antimicrobial-resistant bacteria and the global repercussions of this resistance are emerging as one of the most significant threats to public health. The global scope of the problem is discussed, with recent data showing that antimicrobial resistance (AMR) causes over a million fatalities annually, and projections suggest that this number will rise sharply by 2050. This review aims to provide a comprehensive analysis of this issue, focusing on the mechanisms of antibiotic resistance, its impact on public health and the economy, proposed strategies for addressing the problem, and potential alternative therapeutic approaches. This review is based on a thorough examination of current publications from the World Health Organization (WHO), European Centre for Disease Prevention and Control (ECDC), and relevant scientific literature obtained from databases such as PubMed. The primary objective of this publication is to highlight the escalating nature of this problem and to promote education and awareness in this critical area of healthcare.